Comparison of Employee Work Experiences in the Creative Field with Work from Home Systems and Full Office Systems - Divani Fitria Nuraini; Zandra Dwanita Widodo; Atik Lusia (ProBisnis : Jurnal Manajemen, 2026)
This research is motivated by the new work system in Indonesia due to the COVID-19 pandemic. This new work system is commonly referred to as work from home (WFH). This study aims to compare the work experiences of creative workers under WFH and WFO systems. This study used a qualitative approach with phenomenological methods. Data were collected through interviews with creative workers in Malang and Yogyakarta. Data analysis was conducted using thematic analysis with the help of the NVivo application. The results of this study indicate that WFH work offers flexible hours but can have both positive and negative impacts, such as blurred work hour boundaries and a heavy workload. However, the positive impact is that some creative workers have more freedom to seek ideas and inspiration Meanwhile, the analysis revealed that the WFO work system has a workflow and predetermined working hours, so the boundaries between work and personal life are not blurred. However, this can sometimes lead to creative workers feeling bored. The conclusion of this study shows that both work systems have advantages and disadvantages. It depends on how we choose.